2007
DOI: 10.1016/j.immuni.2007.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Lymphoid-Organ Development Occurs through Interleukin 7-Mediated Enhanced Survival of Lymphoid-Tissue-Inducer Cells

Abstract: Development of Peyer's patches and lymph nodes requires the interaction between CD4+ CD3- IL-7Ralpha+ lymphoid-tissue inducer (LTi) and VCAM-1+ organizer cells. Here we showed that by promoting their survival, enhanced expression of interleukin-7 (IL-7) in transgenic mice resulted in accumulation of LTi cells. With increased IL-7 availability, de novo formation of VCAM-1+ Peyer's patch anlagen occurred along the entire fetal gut resulting in a 5-fold increase in Peyer's patch numbers. IL-7 overexpression also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(162 citation statements)
references
References 41 publications
8
153
1
Order By: Relevance
“…ILC2 and ILC3 are IL-7Ra + and these ILC subsets are strongly reduced in the absence of IL-7 (2). During both fetal and adult life, IL-7 signaling regulates the size of the LTi cell pool by promoting cell survival (60)(61)(62). In a similar fashion, IL-7 may sustain the homeostasis of ILC2 and NCR + ILC3.…”
Section: Factors Regulating Ilc Homeostasis and Functionmentioning
confidence: 99%
“…ILC2 and ILC3 are IL-7Ra + and these ILC subsets are strongly reduced in the absence of IL-7 (2). During both fetal and adult life, IL-7 signaling regulates the size of the LTi cell pool by promoting cell survival (60)(61)(62). In a similar fashion, IL-7 may sustain the homeostasis of ILC2 and NCR + ILC3.…”
Section: Factors Regulating Ilc Homeostasis and Functionmentioning
confidence: 99%
“…The adoptive transfer of adult CD4 + CD3 − LTi cells into Cxcr5 −/− mice induces the development of intestinal lymphoid tissues 31. Similarly, the increased availability of IL‐7 in transgenic mice has been associated with the LTi cell‐dependent development of additional Peyer's patches, caecal patches and de novo formation of ectopic lymphoid organs 32. A recent study has also shown that IL‐17 induces CXCL12 and iBALT development in response to Pseudomonas aeruginosa infection, where the main source of IL‐17 was γδ T cells (T γδ 17 cells) 33.…”
Section: Cellular Initiators Of Ectopic Lymphoneogenesismentioning
confidence: 99%
“…1A). We have previously shown that IL-7 is crucial for LTi cell (45) and LN development (31) and that, in addition to IL-7, other cytokines promote intestinal LTi cell and PP development (29,31). To investigate whether Flt3L has an influence on LTi cell development, we analyzed fetal and neonatal flt3l 2/2 mice and compared them with WT and Il7 2/2 mice.…”
Section: Flt3l Regulates Intestinal Lti Cell Numbers and Pp Developmentmentioning
confidence: 99%